02.47 Strong age-dependent effects of dopamine on synovial fibroblast migration in rheumatoid arthritis and osteoarthritis patients. (1st March 2017) - Nie, Lina van; Rehart, Stefan; Neumann, Elena; Müller-Ladner, Ulf; Capellino, Silvia
Abstract : Background: To keep synovial fibroblasts (SF) from migrating into the adjacent cartilage is a desirable therapeutic target in rheumatoid arthritis (RA). Using this approach, both joint destruction and disability could be prevented. Moreover, our previous studies could show a significant decrease of IL-6 and IL-8 in RASF under dopamine receptor activation ( Capellino S et al, Arthritis Rheumatol 2014 ). Based on these results, we suggest a potential impact of RASF on joint invasion and destruction in RA. Materials and methods: RA and osteoarthritis (OA) SF were obtained from patients undergoing knee joint replacement surgery (mean age: OA: 74.3±11.3 years; RA: 73.7±10.3 years).In order to investigate the dopamine receptor (DR) distribution in the synovium, we performed immunohistochemistry and evaluated all DR 5 receptor subtypes. Here, the DR-expression in the lining layer and especially in the invasion zone between was of special interest. SF migration and motility assays as well as ELISAs for MMP3 and proMMP1 were performed under D1-like (D1DR and D5DR) and D2-like (D2DR, D3DR and D4DR) receptor stimulation, each in different concentrations, respectively. Results: D1DR, D4DR and D5DR were higher expressed on SF nearby the invasion zone. Also, migration of RASF and OASF were found to be correlated with age of the patient at surgery. While younger patients (≤75 years) showed an increase in migration up to 78%, the older patients (≥75 years) show a reduced migration of less than 50% (p=0.0009; r=0.69, OA n=8; RA n=7). No difference could be observed between RA and OA patients and between the D1-like and D2-like receptor stimulation. The same impact on the RASF and OASF could be seen in the motility assay (OA n=6; RA n=6). MMP3 and proMMP1 level were altered in both directions under DR activation (OA n=3; RA n=3). Conclusion: DRs are highly expressed in the invasion zone, which suggests a direct role for dopamine on the aggressive phenotype of the synovial fibroblasts, as confirmed in the in vitro assays. As RASF migration is significantly altered under DR activation, the synovial dopamine pathway can be regarded as a potential therapeutic target of RA.